Control of CDH1/E-Cadherin Gene Expression and Release of a Soluble Form of E-Cadherin in SARS-CoV-2 Infected Caco-2 Intestinal Cells: Physiopathological Consequences for the Intestinal Forms of COVID-19 - Osman, Ikram Omar; Garrec, Clémence; de Souza, Gabriel Augusto Pires; Zarubica, Ana; Belhaouari, Djamal Brahim; Baudoin, Jean-Pierre; Lepidi, Hubert; Mege, Jean-Louis; Malissen, Bernard; Scola, Bernard La; Devaux, Christian Albert (Frontiers in Cellular and Infection Microbiology, 2022)
COVID-19 is the biggest pandemic the world has seen this century. Alongside the respiratory damage observed in patients with severe forms of the disease, gastrointestinal symptoms have been frequently reported. These symptoms (e.g., diarrhoea), sometimes precede the development of respiratory tract illnesses, as if the digestive tract was a major target during early SARS-CoV-2 dissemination. We hypothesize that in patients carrying intestinal SARS-CoV-2, the virus may trigger epithelial barrier damage through the disruption of E-cadherin (E-cad) adherens junctions, thereby contributing to the overall gastrointestinal symptoms of COVID-19. Here, we use an intestinal Caco-2 cell line of human origin which expresses the viral receptor/co-receptor as well as the membrane anchored cell surface adhesion protein E-cad to investigate the expression of E-cad after exposure to SARS-CoV-2. We found that the expression of CDH1/E-cad mRNA was significantly lower in cells infected with SARS-CoV-2 at 24 hours post-infection, compared to virus-free Caco-2 cells. The viral receptor ACE2 mRNA expression was specifically down-regulated in SARS-CoV-2-infected Caco-2 cells, while it remained stable in HCoV-OC43-infected Caco-2 cells, a virus which uses HLA class I instead of ACE2 to enter cells. It is worth noting that SARS-CoV-2 induces lower transcription of TMPRSS2 (involved in viral entry) and higher expression of B0AT1 mRNA (that encodes a protein known to co-express with ACE2 on intestinal cells). At 48 hours post-exposure to the virus, we also detected a small but significant increase of soluble E-cad protein (sE-cad) in the culture supernatant of SARS-CoV-2-infected Caco-2 cells. The increase of sE-cad release was also found in the intestinal HT29 cell line when infected by SARS-CoV-2. Beside the dysregulation of E-cad, SARS-CoV-2 infection of Caco-2 cells also leads to the dysregulation of other cell adhesion proteins (occludin, JAMA-A, zonulin, connexin-43 and PECAM-1). Taken together, these results shed light on the fact that infection of Caco-2 cells with SARS-CoV-2 affects tight-, adherens-, and gap-junctions. Moreover, intestinal tissues damage was associated to the intranasal SARS-CoV-2 infection in human ACE2 transgenic mice.